The effect of tension compression asymmetry on modelling the bending response of sheet moulding compound composites. (1st December 2018) - Tham, Jonathan; Sabiston, Trevor; Trauth, Anna; Lévesque, Julie; Weidenmann, Kay André; Inal, Kaan
Abstract: Phenomenological models are required to predict the behaviour of a glass fibre reinforced Sheet Moulding Compound (SMC) composite material for use in the automotive industry. Material testing is conducted in tension, compression, in-plane shear, and three-point bending. The SMC composite exhibits tension-compression asymmetry and in-plane anisotropy. A model, which incorporates an anisotropic and asymmetric yield function, is developed. The model is calibrated to the experimental tension, compression and in-plane shear tests and are validated using the three-point flexure test. The model captures the flexure response within 8.1% of the experimental observations. The importance of including tension compression asymmetry within the model is demonstrated.